Design of Automatic Mujair Fish Feed Based on Arduino And Telegram - Moch Nando Askitha Videnta; Misbah Misbah; Denny Irawan (Indonesian Vocational Research Journal, 2021)
The need for fish consumption in East Java Province in 2012 reached 24.55 kg/capita/year.With a fish consumption rate of 24.55 kg/capita/year, East Java Province must provide 925,139 tons offish to meet the fish consumption of its population within a year. However, considering that theproduction of catch fisheries has decreased due to overfishing. The RPJMN emphasizes the importanceof increasing production from aquaculture, because the potential for land that can be developed forcultivation is still large. This makes land fish farming more intensively developed.Therefore, the final project will be entitled "Design of Automatic Mujair Fish Feed Based on Arduino andTelegram" this system works to regulate the distribution of fish feed automatically. The design of thisautomatic feeder uses Esp 32 as the main control which is used to regulate the operation of theautomatic tilapia fish feed machine. This tool uses a pH sensor and a water turbidity sensor. The bloweris useful for spreading feed and the Ph sensor (PH-4502C) as a water level reader if the water content isbelow average it will turn on the neutralizing water pump, the water turbidity sensor as a reader of theintensity of cloudy water in the pond, after that Esp 32 processes the data and send via telegram to sendnotification messages.From this study, it shows effective and efficient results because it can save the time of the pool owner.With the advantage of a data report that can be received directly to the pool owner via the telegrammessenger application.